Study and development of nanostructured metals for production of medical implants and equipment - Валиев R. Z.; Парфенов E. V.; Рааб G. I.; Семенова I. P. (Materials. Technologies. Design)
Nanostructured metals (Ti and Ti alloys, stainless steels, Mg alloys) with enhanced static and fatigue strengths are promising materials for medical implants [1]. The use of a combined severe plastic deformation (SPD) processing, including the recent equal channel angular pressing (ECAP)-Conform technique leads to significant strengthening of metallic materials due to their nanostructuring. In particular, the use of nanoTi rods with enhanced strength and fatigue life have enabled the fabrication of implants with improved design for dentistry and orthopedics. Furthermore, surface modification of nanoTi through chemical etching and bioactive coatings allows for considerable improvement of its biomedical properties. As a result of conducted studies, miniaturized dental implants and nanoTi plates with reduced thickness and enhanced osseointegration were manufactured and successfully tested in clinical trials.